Akses Toilet Sehat Ramah Anak Dan Lingkungan Dalam Implementasi Program Perilaku Hidup Bersih dan Sehat (PHBS) Anak Usia Dini Di Pos PAUD Terpadu Melati - Endang Susilowati; Alfi Rohmatul Hidayah; Muhammad Ubaidillah Al Mustofa; Arwi Yudhi Koswara; Mashudi; S. Kamilia Aziz; Arfan Fahmi (Pusat Publikasi ITS, 2026)
This Community Service Program (Program Pengabdian Masyarakat/PPM), initiated by the PPM team of Institut Teknologi Sepuluh Nopember (ITS), was implemented at Pos PAUD Terpadu Melati, Medokan Ayu Sub-district, Surabaya City. The program aimed to enhance the implementation of Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) in early childhood education settings through the development of child-friendly and hygienic toilet infrastructure, as well as hygiene education for young children. The implementation method consisted of four stages: (1) field-based problem identification through surveys and focus group discussions (FGDs); (2) program implementation, including the construction of child-friendly toilet facilities and PHBS educational training; (3) evaluation of program implementation; and (4) development of a sustainability system through educational products and scientific publications. The results indicate that the program received positive responses from the Medokan Ayu local government, teachers, parents, and children in utilizing the newly developed facilities. This program is expected to serve as a good practice that can be widely adapted to support the creation of healthy, safe, and sustainable learning environments for early childhood education.